From Second Bull Run to Gettysburg : the Civil War in the east, 1862-63 - Stackpole, Edward J. (Edward James), 1894-1967 (Stackpole Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2018)
Stackpole Books presents Gen. Edward J. Stackpole's Civil War classics -- They Met at Gettysburg, Drama on the Rappahannock, Chancellorsville, and From Cedar Mountain to Antietam -- in a single abridged volume that covers the war's pivotal and turbulent middle year in the Eastern Theater, from the summer of 1862 through the summer of 1863. This year of bloody conflict included the war's defining battles: Second Bull Run, Antietam, Fredericksburg, Chancellorsville, and Gettysburg. It was a year during which the Union cycled through generals as Lincoln sought one who could fight and win.